Hybrid molecularly imprinted polymers modified by deep eutectic solvents and ionic liquids with three templates for the rapid simultaneous purification of rutin, scoparone, and quercetin from Herba Artemisiae Scopariae. Issue 23 (2nd November 2016) - Li, Guizhen; Ahn, Wha Seung; Row, Kyung Ho
Abstract : Different kinds of deep eutectic solvents based on choline chloride and ionic liquids based on 1‐methylimidazole were used to modify hybrid molecularly imprinted polymers with the monomer γ‐aminopropyltriethoxysilane‐methacrylic and three templates (rutin, scoparone, and quercetin). The materials were adopted as solid‐phase extraction packing agents, and were characterized by FTIR spectroscopy and field emission scanning electron microscopy. The hybrid molecularly imprinted polymers modified by deep eutectic solvents had high recoveries and a strong recognition of rutin, scoparone, and quercetin in Herba Artemisiae Scopariae than those modified by ionic liquids. In the procedure of solid‐phase extraction, deep eutectic solvents‐2‐hybrid molecularly imprinted polymers were obtained with the best recoveries with rutin (92.27%), scoparone (87.51%), and quercetin (80.02%), and the actual extraction yields of rutin (5.6 mg/g), scoparone (2.3 mg/g), and quercetin (3.4 mg/g). Overall, the proposed approach with the high affinity of hybrid molecularly imprinted polymers might offer a novel method for the purification of complex samples.